Comparison of the rare earth element trophodynamics between freshwater and coastal species from the upper Yellow River to estuary: Insights into health risk - Xiang Gu; Maoshan Lian; Chunye Lin; Zhongmin Lian; Xiaoli Zhao; Fengchang Wu (Environment International)
Rare earth elements (REEs) are currently considered as contaminants of emerging concern, but their residual levels and trophic transfer in aquatic species and potential health risks are not fully characterized. This study compared the distribution patterns and trophodynamics of 15 REEs in the wild species of the Yellow River and adjacent Laizhou Bay of northern China. The daily intake of REEs through consuming aquatic products for Chinese residents was also estimated. The squids were characterized by the highest REE concentrations (5779–6102 μg/kg), followed by the sea snails, shrimps and crabs, and both the coastal and freshwater fish. Among different tissues of the Silurus lanzhouensis, gill played an important role in accumulating REEs and detoxication. The Eu and Ce anomalies of the aquatic organisms were consistent with those in sediments of their living habits, showing a common lithogenic origin. According to the bioaccumulation factor, no obvious bioaccumulation of REEs was observed for these aquatic species. Importantly, the relationships between the REEs and stable nitrogen isotopes (δ15N) suggested a significant trophic dilution of REEs in the coastal organisms. The estimated daily intake of REEs from consuming the aquatic organisms were relatively low, indicating the negligible health risk for Chinese adults. These results provide improved insights into the trophodynamics of REEs in the aquatic organisms and potential human health risks of REEs from consuming the aquatic products in China.